DAMPAK INFLASI TERHADAP PERTUMBUHAN EKONOMI: TINJAUAN LITERATUR - Caesar Muslim; Ikrar Muadsim; Zainuddin Saenong; Nur Azisah; Ilyas (Universitas Tabanan, 2026)
This study aims to identify challenges in understanding the impact of inflation on economic growth in Indonesia and provide policy recommendations that can support the formulation of more effective and sustainable economic policies. The method used is a systematic literature review (SLR) with the primary data source from Google Scholar, which has a broad and relevant scientific literature coverage. A step-by-step filtering was carried out based on relevance and publication years 2010–2025. The analysis was conducted descriptively to interpret the relationship between inflation and Indonesia's economic growth. The results of the study indicate that inflation has a complex influence, where moderate inflation can encourage economic growth, while high inflation tends to hinder it by reducing purchasing power, investment, and macroeconomic stability. In conclusion, inflation stability is a key factor in supporting sustainable economic growth, so that synergy of adaptive and integrated monetary and fiscal policies is needed.